2020
DOI: 10.1001/jamanetworkopen.2020.13940
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cytoreductive Surgery With or Without Hyperthermic Intraperitoneal Chemotherapy for Stage III Epithelial Ovarian Cancer

Abstract: Key Points Question Is the addition of hyperthermic intraperitoneal chemotherapy (HIPEC) to primary cytoreductive surgery (PCS) associated with better outcomes for patients with stage III epithelial ovarian cancer? Findings In this multicenter retrospective cohort study of 584 patients with stage III epithelial ovarian cancer, for patients undergoing PCS with HIPEC and those undergoing PCS alone, the median overall survival was 49.8 and 34.0 months, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 37 publications
0
52
0
2
Order By: Relevance
“…Examples of this concept are provided in Figure 3. This finding has potential implications for efficacy of regional therapeutic strategies, such as intraperitoneal administration of chemotherapy in women with advanced epithelial ovarian carcinomas (65). One example of the potential importance of TNT-mediated cell tethering of spheroids is that it would facilitate direct TNT-specific cell-to-cell communication in the evolution of resistance to this treatment, in a more specific manner than EVs can perform in this fluid-filled environment.…”
Section: Peritoneal Cancers Including Ovarian Carcinoma and Malignanmentioning
confidence: 98%
“…Examples of this concept are provided in Figure 3. This finding has potential implications for efficacy of regional therapeutic strategies, such as intraperitoneal administration of chemotherapy in women with advanced epithelial ovarian carcinomas (65). One example of the potential importance of TNT-mediated cell tethering of spheroids is that it would facilitate direct TNT-specific cell-to-cell communication in the evolution of resistance to this treatment, in a more specific manner than EVs can perform in this fluid-filled environment.…”
Section: Peritoneal Cancers Including Ovarian Carcinoma and Malignanmentioning
confidence: 98%
“…Lei et al [49] perfomed a cohort study from January 2010 to May 2017 at 5 high-volume institutions in China to compare survival outcomes between PCS with HIPEC vs. PCS alone for patients with stage III epithelial ovarian cancer. A total of 584 patients with stage III primary epithelial ovarian cancer were treated with either PCS alone or PCS with HIPEC.…”
Section: Review and Discussionmentioning
confidence: 99%
“…International groups agree that these women should only receive HIPEC within a clinical trial 16 . A recent retrospective cohort study of 584 women who underwent up‐front surgery for stage III ovarian cancer showed significantly improved survival in the HIPEC arm (49.8 months vs 34.0 months, HR = 0.63, 95%CI, 0.49–0.82, P < 0.001) 17 . However, caution is required in interpreting these results due to potential confounders of a non‐randomised trial.…”
Section: What Is the Current Evidence For Hipec For The Treatment Of mentioning
confidence: 99%